2013
DOI: 10.3168/jds.2011-5225
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bayesian least absolute shrinkage and selection operator (LASSO) and BayesCπ methods for genomic selection in French Holstein and Montbéliarde breeds

Abstract: Recently, the amount of available single nucleotide polymorphism (SNP) marker data has considerably increased in dairy cattle breeds, both for research purposes and for application in commercial breeding and selection programs. Bayesian methods are currently used in the genomic evaluation of dairy cattle to handle very large sets of explanatory variables with a limited number of observations. In this study, we applied 2 bayesian methods, BayesCπ and bayesian least absolute shrinkage and selection operator (LAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 39 publications
(46 reference statements)
1
34
2
1
Order By: Relevance
“…Some of these studies do not agree with the trend of deflation we observed here (e.g. [12,45]), while other methods similar to BayesC and BLASSO also resulted in deflated predictions for some traits analyzed [9,11,46]. This variation in scale may be related to differences inherent to the data analyzed (e.g.…”
Section: Discussioncontrasting
confidence: 69%
“…Some of these studies do not agree with the trend of deflation we observed here (e.g. [12,45]), while other methods similar to BayesC and BLASSO also resulted in deflated predictions for some traits analyzed [9,11,46]. This variation in scale may be related to differences inherent to the data analyzed (e.g.…”
Section: Discussioncontrasting
confidence: 69%
“…It refers to a genetic evaluation method that uses phenotypic data and genotypes of dense single nucleotide polymorphisms (SNPs) to estimate effects of SNPs from a training population and subsequently to predict the genetic values of selection candidates based on their genotypes [8]. It has been widely applied to dairy cattle breeding [911] and is now beginning to be used in other livestock species [12, 13]. Genomic predictions for beef cattle are attractive because many traits that affect the profitability of beef production, such as carcass traits, are difficult to select for because they are expensive to measure or are measured only on the relatives of breeding bulls [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the BMA needs a priori information to build a fair predictive model. The LASSO is based on shrinkage estimation and has been widely used in the statistical field [12][16]. The advantages of LASSO include: 1) a smaller mean squared error (MSE) than conventional methods; 2) it handles the multicollinearity problem; 3) overall variable selection; and 4) coefficients shrink [9][11].…”
Section: Introductionmentioning
confidence: 99%